The Quality Of The Learning Environment In Government Preschools In Jordan - Aldrab'ah, Intisar Turki Salamah (2011)
This study is undertaken to assess the status of the quality of the learning environment in government preschools in Jordan in terms of Space and Furnishing; Personal Care Routines; Language-Reasoning; Activities; Interaction; Program Structure; and Parents and Staff. The study also looked at the strengths and weaknesses of the learning environment. Further, it examined if there were significant differences in the quality based on location of preschools and teacher’s experience and looked for the ways in which the quality of the learning environment could be improved.